Sentencing the drug offender practice in the Magistrates' courts in Malaysia / Mohd Fadhir Harun - Harun, Mohd Fadhir (Faculty of Law, 1986)
Different interpretation can be given and to some of the terms used in this paper and to avoid confusion, ambiguity and misunderstanding the meaning attributed to this misunderstanding the meaning attributed to this paper or terms for the purpose of this paper will be defined and laid down here. A ‘sentence’ is a disposition which the court order after a person is found guilty and or the convicted of an offence. ‘Sentencing’ refer to the process in a trial after a person is found guilty and or convicted of an offence. Sentencing thus involve a consideration of pre-sentence reports, consideration of extenuation of other matter pertaining to deciding an appropriate sentence.